PENGARUH KONSUMSI SUSU KEDELAI TERHADAP PENINGKATAN PRODUKSI ASI PADA POSTPARTUM DI PMB I BOGOR TAHUN 2021 - Rusdi, Annisa (Politeknik Tiara Bunda, 2024)
Background: Breast milk (ASI) is recognized as the best source of nutrition for babies during the first six months of their life because of its energy and essential substance content. Research Objective: This study aims to assess the effect of giving soy milk on breast milk production in postpartum mothers at PMB Irna Maya Bogor in 2023. Research Method: This research is a quantitative study with a population and sample of 20 postpartum mothers at PMB Irna Maya Sari Bogor in August. Data were analyzed using statistical tests. Research Results: The results of the research show that giving soy milk can increase the smoothness of breast milk production, with 10 respondents (50%) experiencing an increase. The p-value is 0.000 < 0.05, indicating that there is a significant relationship between giving soy milk and smooth breast milk production at PMB Irna Maya in 2021. Conclusion: Based on the research results, it can be concluded that giving soy milk has a positive influence in increasing breast milk production in postpartum mothers at PMB Irna Maya Bogor in 2021